2004
DOI: 10.1023/b:biog.0000031053.81520.db
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microrelief and vegetation on methane emission from wet polygonal tundra, Lena Delta, Northern Siberia

Abstract: Abstract. The effect of microrelief and vegetation on methane (CH 4 ) emission was investigated in a wet polygonal tundra of the Lena Delta, Northern Siberia (72.37N, 126.47E). Total and plant-mediated CH 4 fluxes were measured by closed-chamber techniques at two typical sites within a low-centred polygon. During the study period, total CH 4 flux averaged 28.0 AE 5.4 mg m À2 d À1 in the depressed polygon centre and only 4.3 AE 0.8 mg m À2 d À1 at the elevated polygon rim. This substantial small-scale spatial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
230
3
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(260 citation statements)
references
References 50 publications
23
230
3
4
Order By: Relevance
“…More detailed descriptions of the vegetation and landscape characteristics are available; cf. Are and Reimnitz (2000), Kutzbach et al (2004Kutzbach et al ( , 2007, Boike et al (2008) and Sachs et al (2008).…”
Section: Study Sitementioning
confidence: 99%
“…More detailed descriptions of the vegetation and landscape characteristics are available; cf. Are and Reimnitz (2000), Kutzbach et al (2004Kutzbach et al ( , 2007, Boike et al (2008) and Sachs et al (2008).…”
Section: Study Sitementioning
confidence: 99%
“…It seems likely that the peak emissions from the floating mat were caused by an optimum of wet conditions in the peat, favoring methanogenesis and impeding methane oxidation, presence of some Carex aquatilis providing for conduit transport of the gas, and potentially by a release of methane from groundwater entering the land-water interface. CH 4 flux through plants with aerenchymatic tissues can be responsible for 50 to 97 % of the total CH 4 flux in peatlands because the aerenchyma link the anaerobic zone of CH 4 production with the atmosphere (Kelker and Chanton, 1997;Kutzbach et al, 2004;Shannon et al, 1996). Kutzbach et al (2004) found a strong positive correlation between the density of C. aquatilis culms and CH 4 fluxes, as well as a contribution of 66 ± 20 % of the plant-mediated CH 4 flux through C. aquatilis to the total flux in wet polygonal tundra.…”
Section: Spatial Pattern Of Ch 4 and Co 2 Fluxesmentioning
confidence: 99%
“…CH 4 flux through plants with aerenchymatic tissues can be responsible for 50 to 97 % of the total CH 4 flux in peatlands because the aerenchyma link the anaerobic zone of CH 4 production with the atmosphere (Kelker and Chanton, 1997;Kutzbach et al, 2004;Shannon et al, 1996). Kutzbach et al (2004) found a strong positive correlation between the density of C. aquatilis culms and CH 4 fluxes, as well as a contribution of 66 ± 20 % of the plant-mediated CH 4 flux through C. aquatilis to the total flux in wet polygonal tundra. Since ebullition dominated the CH 4 flux from the floating mat (Fig.…”
Section: Spatial Pattern Of Ch 4 and Co 2 Fluxesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of cryopedogenesis, many permafrost soils are influenced by a strong micro-relief (e.g. low-centered ice-wedge polygons), which causes small-scale variations in soil types and vegetation characteristics (Kutzbach et al 2004), as well as in the microclimatic conditions (Boike et al 2008). This affects the abundance, processes and diversity of the methanogenic community in this habitat.…”
Section: The Permafrost Environmentmentioning
confidence: 99%